(3OdGFd GdQCS hGdPfH hPhGJ GdPhGFH aj JMGhjd GdSfjfs - (3LYaQ Hf eMeO Hf YeQ GdHdNj, CHh eYTQ , nCoHh nerYnTQ Gdnandcj,J (B272 (3g` s ((3MGLi Ydi GdQGRi s)
(3ChdgG (B:s
(3HGH ai eYQaI eG jOd Ydjg GdQCS hGdPfH hPhGJ GdPhGFH HchfgG ai GdHQhL ai Mjf WdhY GdSfI EPG cGf GdQCS ai GdMed ESJYdGA GdYXeGA s
(3BNQgG (B:s
(3aGfXQ Edi SeJ PfHg ai Ci fGMjI , hef Jdc GdfGMjI jchf eG jOd Ydjg heG hUaJg hGdchcH GdPi WHYg ai GdaYd WHY GdMGOKI EfeG jchf HJdc GdSfI , aGYdeg Je GdcJGH GdKGfi HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3cJHgG GdfGSN Yf fSNI LeYgG EHQGgje GdMGSH GdeGdci GdefUhQi GdfGUQi HeOjfI GdbGgQI SfI (B759(3g`s
(3HChd GdeLehYI Jedc SfI (B1249(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs